Storage and binding of object features in visual working memory. - Bays, P; Wu, E; Husain, M (2011)
An influential conception of visual working memory is of a small number of discrete memory "slots", each storing an integrated representation of a single visual object, including all its component features. When a scene contains more objects than there are slots, visual attention controls which objects gain access to memory. A key prediction of such a model is that the absolute error in recalling multiple features of the same object will be correlated, because features belonging to an attended object are all stored, bound together. Here, we tested participants' ability to reproduce from memory both the color and orientation of an object indicated by a location cue. We observed strong independence of errors between feature dimensions even for large memory arrays (6 items), inconsistent with an upper limit on the number of objects held in memory. Examining the pattern of responses in each dimension revealed a gaussian distribution of error centered on the target value that increased in width under higher memory loads. For large arrays, a subset of responses were not centered on the target but instead predominantly corresponded to mistakenly reproducing one of the other features held in memory. These misreporting responses again occurred independently in each feature dimension, consistent with 'misbinding' due to errors in maintaining the binding information that assigns features to objects. The results support a shared-resource model of working memory, in which increasing memory load incrementally degrades storage of visual information, reducing the fidelity with which both object features and feature bindings are maintained.